Perancangan Website Sebagai Media Promosi Dan Penjualan Pada Home Industry Abon - Dewi, Shanty Kusuma; Garside, Annisa Kesy (Jurnal Teknik Industri, 2014)
Marketing activity which is performed by a home industry of abon namely Lestari Jaya Pangan currently is not completely well established. Selling activity is conventionally run through offering the product to stores, market and also through retailer. Its affects the sale to be limited only nearby region of Malang. Promotion strategy also limited by using brochure and participating either local or national fair which is organized by goverment. In order to tackle the issue, the website is needed to be designed to support marketing and selling activity of its product particularly abon. website is designed by using oneline selling system with content management system (CMS) opencart. Through the website, marketing activity is more effective and able to increase income.